Provision of Public Goods in an Islamic Economy (The Pakistan Development Review, 1995)
Islam establishes a welfare society. It obligates the society to make arrangements for need-fulfilment of all citizens. The Islamic economy working with the market and non-market institutions and guided by Islamic values meets the personal and public needs of its people. The market system in a secular economy under appropriate conditions can efficiently meet personal needs of the people; however, it fails to do so in case of public goods. While supplementing the market system with other institutions, the Islamic economy manages to supply optimal quantity of the public goods. The paper studies this issue in the light of the Qur'an, the Sunnah, and Islamic history. I